2011
DOI: 10.1002/wmts.23
|View full text |Cite
|
Sign up to set email alerts
|

Kainate receptor trafficking

Abstract: Kainate receptors (KARs) are ligand-gated ion channels that can regulate neuronal network activity and are involved in processes ranging from neuronal development and differentiation to neurodegeneration and neuronal cell death. They are tetrameric assemblies which can comprise different subunit combinations and are differentially targeted to specific cell surface compartments including preand postsynaptic membranes where they perform distinct functional roles. The processes regulating the constitutive and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…Although there is a strong base of knowledge about the activity-dependent regulation of KAR endocytosis and recycling [13,15,[67][68][69][70][71], compared to AMPARs [72] and tsVSVG cargo [73], little is known about the activitydependence of secretory pathway trafficking of KARs. A very recent study reported that secretory pathway KAR trafficking is indeed highly regulated in multiple different cellular activity contexts [48].…”
Section: Activity Dependent Secretory Pathway Traffickingmentioning
confidence: 99%
“…Although there is a strong base of knowledge about the activity-dependent regulation of KAR endocytosis and recycling [13,15,[67][68][69][70][71], compared to AMPARs [72] and tsVSVG cargo [73], little is known about the activitydependence of secretory pathway trafficking of KARs. A very recent study reported that secretory pathway KAR trafficking is indeed highly regulated in multiple different cellular activity contexts [48].…”
Section: Activity Dependent Secretory Pathway Traffickingmentioning
confidence: 99%
“…Kainate receptors (KARs) are tetrameric assemblies of combinations of GluK1 -GluK5 subunits. They are present at both pre-and postsynaptic membranes where they perform distinct roles in modulating synaptic transmission, neuronal excitability and network activity 5,6 , and are implicated in processes ranging from neuronal development and differentiation to neurodegeneration and neuronal cell death 5,7 . In addition to direct ionotropic signalling, KARs also signal through the activation of G proteins leading to PKC activation 5,6,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…We used the KAR subunit GluK2 as a prototypic iGluR cargo. KARs are present at both pre- and postsynaptic membranes, where they perform distinct roles in modulating synaptic transmission, neuronal excitability, and network activity ( Contractor et al., 2011 , Lerma and Marques, 2013 ), and they are implicated in processes ranging from neuronal development and differentiation to neurodegeneration and neuronal cell death ( Contractor et al., 2011 , González-González et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%